The relational ecology of the transition to parenthood in couples that conceived spontaneously or through Assisted Reproductive Technologies - Gameiro, Carla Sofia Marques Rodrigues (2009)
Tese de doutoramento em Psicologia, especialidade de Psicologia da Saúde, apresentada à Faculdade de Psicologia e Ciências da Educação da Universidade de Coimbra